ASSESSMENT OF LABORATORY PARAMETERS IN PATIENTS WITH UNCOMPLICATED PYELONEPHRITIS (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Background: During a woman’s lifetime, the incidence of experiencing at least one episode of uncomplicated urinary tract infection (UTI) is approximately 30–40%, and in the majority of cases antibiotics are prescribed by physicians during treatment [1]. Routine urinalysis and biochemical testing remain essential for confirming the diagnosis and assessing disease severity.
Keywords: urinary tract infection; leukocyturia; urine specific gravity; urea; glucose; creatinine; total protein